Rasio Otot-Tulang Pectoralis Berbagai Jenis Itik Lokal di Jawa Tengah - Savitri, Ajeng Fatria; Wachidah Yuniwarti, Enny Yusuf; Isdadiyanto, Sri (Bioma : Berkala Ilmiah Biologi, 2016)
Local ducks farm businesses potentially developed as the meat producer, which was expected to fit and complete the nutrition for society. The provision of excellent meat quality was one of the main goals that integrated with the development of animal husbandary. The quality and quantity of meat on the carcass could be seen as one of the indicators of ducks productivity. The study about the influence of various types of ducks to pectoralis meat bone ratio as the component of commercial carcass had to be done to find out about the quality and genetics potentials of every ducks type in order to improve the quality of food. This study aimed to analyze the influence of various types of ducks in Central Java, such as Pengging duck, Tegal duck, and Magelang duck to the carcass quality evaluated from the value of pectoralis meat bone ratio. The ducks used in the study were 6 months. The types of ducks were used as comparison. Samples were taken from the three types of local ducks and the repetition was done six times for each type of ducks. The measured variables were live weight, pectoralis weight, pectoralis percentage, meat bone percentage, and meat bone ratio. The data were analyzed using ANOVA. Real different datas were analyzed by further testing Least Significant Difference Test (LSDT) at the level of 95%. The results showed that various types of local ducks did not significantly affect the value of the pectoralis meat bone ratio, therefore it could be concluded that various local ducks did not affect on pectoralis meat bone ratio.Â Keywords: Local ducks in Central Java, carcass, pectoralis meat bone ratio.